Potential of jet biofuels production and application in Ukraine and Poland. (2015) - Iakovlieva, Anna; Boichenko, Sergii; Vovk, Oksana; Lejda, Kazimierz
The present-day situation in civil aviation is discussed. Taking into account limitation of crude oil resources for jet fuel production and worsening of the ecological situation, the tendency to transition to alternative fuels is presented. The perspectives of Ukraine and Poland in production and application of alternative jet fuels is figured out. Main attention is paid to reveal possibilities of these countries for production of jet biofuels derived from plant oils. The potential of biofuels production from various feedstocks is presented and analysed. The advantages of oil-derived biofuels production and application are discussed.